2017
DOI: 10.18502/kls.v2i6.1021
|View full text |Cite
|
Sign up to set email alerts
|

Towards Developing Salinity Tolerant Rice Adaptable for Coastal Regions in Indonesia

Abstract: Lowland rice areas along the coastal regions are a major contributor for rice production in Indonesia. Sustainability of rice production in those areas is challenged by the increase of soil salinity as the result of sea water inundation. recently which are adaptable to salt affected areas. This paper will describe the progress in the breeding programs to develop salt tolerant rice for lowland rice areas in the coastal regions. Strategy to accelerate the improvement of the salinity tolerant of Indonesian rice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…One well-recognized approach is the adoption of salt tolerant rice in salinity prone areas [17]. Traditional breeding approaches to develop salt tolerant varieties have been applied for a long time, but progress has been slow due to the complexity of salt tolerance mechanism and genotype by environment interactions [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One well-recognized approach is the adoption of salt tolerant rice in salinity prone areas [17]. Traditional breeding approaches to develop salt tolerant varieties have been applied for a long time, but progress has been slow due to the complexity of salt tolerance mechanism and genotype by environment interactions [18].…”
Section: Introductionmentioning
confidence: 99%
“…These two varieties are tolerant to salinity stress at the seedling stage at an EC value of 12 dS m −1 and thus show great potential [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both varieties showed normal growth with no leaf symptoms of salt injury. Inpari-34 and Inpari-35 were more tolerant of salinity stress at seedling stage as found by Hairmansis et al (2017). It was observed that there is no significant difference in germination percentage between cultivar PL-1, PL-2, Inpari 30 and Sidenuk.…”
Section: Germination Percentages and Salt Injury Scorementioning
confidence: 63%
“…Six rice genotypes were used in this study, i.e., (1) Inpari-34 (BR41xIR61920-3B-22-2), (2) Inpari-35 (IR10206-29-212xSUAKOKO), (3) PL-1, (4) PL-2, (5) Inpari-30 (Ciherang sub1), and (6) Sidenuk (Diah Suci variety is irradiated by gamma rays). Inpari 30 and Sidenuk are the modern rice variety used by farmers while Inpari-34 and Inpari-35 were the tolerant variety for saline soils (Hairmansis et al 2017). Two genotypes PL-1 and PL-2 were promising lines to salinity.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation